The Precursor to Glutathione (GSH), γ-Glutamylcysteine (GGC), Can Ameliorate Oxidative Damage and Neuroinflammation Induced by Aβ40 Oligomers in Human Astrocytes - Braidy, Nady; Zarka, Martin; Jugder, Bat-Erdene; Welch, Jeffrey; Jayasena, Tharusha; Chan, Daniel K. Y.; Sachdev, Perminder; Bridge, Wallace (Frontiers in Aging Neuroscience, 2019)
Glutathione (GSH) is one of the most abundant thiol antioxidants in cells. Many chronic and age-related diseases are associated with a decline in cellular GSH levels or impairment in the catalytic activity of the GSH biosynthetic enzyme glutamate cysteine ligase (GCL). γ-glutamylcysteine (GGC), a precursor to glutathione (GSH), can replenish depleted GSH levels under oxidative stress conditions, by circumventing the regulation of GSH biosynthesis and providing the limiting substrate. Soluble amyloid-β (Aβ) oligomers have been shown to induce oxidative stress, synaptic dysfunction and memory deficits which have been reported in Alzheimer’s disease (AD). Calcium ions, which are increased with age and in AD, have been previously reported to enhance the formation of Aβ40 oligomers, which have been casually associated with the pathogenesis of the underlying neurodegenerative condition. In this study, we examined the potential beneficial effects of GGC against exogenous Aβ40 oligomers on biomarkers of apoptosis and cell death, oxidative stress, and neuroinflammation, in human astrocytes. Treatment with Aβ40 oligomers significantly reduced the cell viability and apoptosis of astrocyte brain cultures and increased oxidative modifications of DNA, lipids, and protein, enhanced pro-inflammatory cytokine release and increased the activity of the proteolytic matrix metalloproteinase enzyme, matric metalloproteinase (MMP)-2 and reduced the activity of MMP-9 after 24 h. Co-treatment of Aβ40 oligomers with GGC at 200 μM increased the activity of the antioxidant enzymes superoxide dismutase (SOD) and glutathione peroxidase (GPx) and led to significant increases in the levels of the total antioxidant capacity (TAC) and GSH and reduced the GSSG/GSH ratio. GGC also upregulated the level of the anti-inflammatory cytokine IL-10 and reduced the levels of the pro-inflammatory cytokines (TNF-α, IL-6, and IL-1β) and attenuated the changes in metalloproteinase activity in oligomeric Aβ40-treated astrocytes. Our data provides renewed insight on the beneficial effects of increased GSH levels by GGC in human astrocytes, and identifies yet another potential therapeutic strategy to attenuate the cytotoxic effects of Aβ oligomers in AD.